Analytical tool for optimization of position sensors based on eddy currents effect. Issue 12 (December 2022) - Faria, Andreia; Marques, Luís; Vale, Luís; Ferreira, Carlos; Alves, Filipe; Cabral, Jorge
Abstract: This paper proposes an open-source tool for a fast and precise calculation of the inductance of planar coils in the presence of conductive targets. This tool, based on Grover equations, is versatile to any coil and target geometries. The performance of this tool has been validated by comparing the analytical results with experimental data and Finite Element Model (FEM) simulations. When compared with the experimental measurements, the developed analytical model and the FEM simulation retrieved similar results, with differences below 4%. The proposed tool, in addition to requiring less computing resources, is significantly faster than FEM simulations. This shows the effectiveness of the proposed approach for the analytical calculation of the inductance of planar coils in the presence of conductive plates. It combines accuracy, versatility, speed, and no need for high computational resources. Abstract : Planar coil; Mutual-inductance; Analytical tool; Eddy current; Finite element method; Target.